P391Estimated glomerular filtration rate levels and risk of stroke in individuals with diabetes mellitus and atrial fibrillation. (18th June 2020) - Westreich, R; Barrett, O; Kezerle, L; Leventer Roberts, M; Avgil Tsadok, M; Akriv, A; Ohana, R; Feldman, B; Haim, M
Abstract: Funding Acknowledgements: pfizer Background: Diabetes mellitus (DM) is associated with increased risk of embolic complications in non-valvular atrial fibrillation (NVAF). Chronic kidney disease (CKD) has been shown in some studies to increase the risk of stroke. This finding is not consistent among all studies. Therefore the relationship between kidney function, diabetes and stroke risk is complex and warrants further investigation. Purpose: To assess the incidence rates and risk of ischemic stroke and mortality by baseline Estimated Glomerular Filtration Rate (eGFR) levels among individuals with AF and DM. Methods: A prospective, historical cohort study using our electronic medical records database. The study population included all members 21 years old, with a first diagnosis of NVAF between January 1, 2010 to December 31, 2016 and a minimal follow-up period of 1 year. Among those patients identified as diabetics, we compared three groups of patients according to eGFR levels at the time of AF diagnosis: eGFR ≥ 60, between 30-60 and ≤ 30 or chronic dialysis or kidney transplant. Results: A total of 17, 567 cases were included in the final analysis, of them, 11013 (62.7%) had eGFR ≥ 60, 4930 (28%) with eGFR between 30-60 and 1624 (9.24%) with eGFR ≤30 . The median age was 75 years (IQR 65-83) with a majority of females in all groups, 52.5%, 51.2% and 55.5% respectively. The incidence of stroke per 100 person-years in the three study groups was: 1.88 in patients with eGFR ≥ 60, 2.69 in patients with eGFR between 30-60 and 3.34 in those with eGFR ≤ 30 . Impaired renal function was associated with increased risk of stroke in univariate analysis, but not found in the adjusted model (Adjusted Hazard Ratio (AHR) = 1.04 95% 0.89-1.23 for eGFR 30-60 and 1.16 95% CI 0.88-1.51 for eGFR ≤ 30 compared to GFR ≥ 60). incidence of mortality per 100 person-years was 10.78 in patients with eGFR ≥ 60, 21.49 in patients with eGFR 30-60 and 41.55 in those with eGFR ≤ 30. In both univariate and multivariate analyses, decreased levels of eGFR were associated with increased mortality risk compared to subjects with normal renal function (AHR 1.22 95%CI 1.14-1.27 and AHR 2.09 95%CI 1.95-2.24 for eGFR between 30-60 and for eGFR ≤ 30, respectively). Conclusion: In this observational prospective cohort of patients with newly diagnosed NVAF, impaired renal function was not found to be associated with increased risk of stroke. Lower eGFR levels were associated with an increased mortality risk.